Persepsi Petani terhadap Ketersediaan Sarana dan Prasarana Usahatani di Subak Babakan Bengkel I Desa Getasan Kecamatan Petang Kabupaten Badung - ARYADHANA, I GEDE BAGUS; ASTITI, NI WAYAN SRI; SUARDI, I DEWA PUTU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018DO - 10.24843/JAA.2018.v07.i03.p09, 2018)
Perception Farmers Against Availability Infrastructures in Subak Babakan Bengkel I Village Getasan Sub District Petang Badung. Agriculture in a broad sense includes smallholder agriculture, plantation, forestry, animal husbandry and fishery. Facilities and infrastructure are all things that are used as a tool in achieving the objectives of farmers in Subak Babakan Bengkel I Village Getasan to support developments in running the farm. Based on this expected that the developments in the availability of facilities and infrastructure in the farming. Based on the above problems, the purpose of this study was to determine the perception of farmers on the availability of facilities and infrastructure of farming in Subak Babakan Bengkel I Village Getasan Sub District Petang Badung. To prepare a good questionnaire required some testing prior to conducting the study. Testing the questionnaire using SPSS. The variable in this study is the perception of farmers on the availability of facilities and infrastructure of farming in Subak Babakan Bengkel I Village Getasan Sub District Petang Badung. Indicators of this study include the availability of means of production, namely seeds, fertilizers, pesticides, plant growth regulator and inoculant. Alsintan (agricultural machinery), ie sprayer, power weeder, emposan tikus, reaper, tractors and power threaser. Network infrastructure includes farm roads, halls Subak, and irrigation canals. To maintain and increase the availability of facilities and infrastructure in Subak Babakan Bengkel I of both categories should be excellent farmers complementary facilities and infrastructure that can greatly help in a time efficient and agricultural work in Subak